(untitled) (Psicologia USP, 2021)
This article discusses the use of psychoanalysis – particularly of psychoanalytic technique based on free association – for investigations in the field of social psychology, based on the authors’ experience in a graduate program. To this end, we have attempted to produce a reflection on the conditions and the impact of the dislocation of concepts between the clinic of individual psychic suffering and empirical research involving institutions and groups. By focusing on the assertion of the primacy of the unconscious, we have tried to array the lines of approximation and distancing between clinical practice and empirical research. The basis is the discussion on the necessary conditions (outside of the therapeutic setting) for listening to the unconscious, for creating a transference bond, for the work of interpretation of the discourses of subjects and, finally, for the elaboration of unconscious contents and desires – whether by the subjects listened to in this research or by the researchers themselves in their work of theoretical elaboration.